Memilih Makanan Halal di Daerah Minoritas: Bukti Empiris Pada Forum Jual Beli Online Facebook GPI - Nurul Azizah Azzochrah; Nurhafni Aprilia; Fitri Wulandari (Maqrizi: Journal of Economics and Islamic Economics, 2023)
The issue of halalness is a global issue that is always interesting to research. Halal issues are not only discussed in Muslim majority areas, but also in Muslim minority areas. This research aims to determine the indicators used by consumers in determining and deciding on purchasing halal food at the Griya Paniki Indah (Manado) buying and selling forum. The method used in this research is a qualitative descriptive research method, where the researcher tries to describe the conditions that occurred during this research. The data source used in this research is primary data originating from seller and buyer informants. while the secondary data used are texts related to halal products. The data analysis techniques used in this research are reducing data, presenting data and drawing conclusions. The research results show that the indicators for choosing halal food in minority areas are the religious attributes and captions used by buyers